Principal Supervision In Elementary Schools - Tooy, Olivia A.; Sumual, Tinneke E. M.; Tiwa, Tellma M. (Abdurrauf Science and Society, 2025)
This study aims to analyze the principal's academic supervision at the Watutumou Inpres Elementary School. The focus of this study covers four stages of academic supervision, namely planning, implementation, and follow-up. The research method used is a descriptive qualitative approach with interviews, observation, and documentation techniques. Data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the principal in carrying out supervision is quite good at implementing academic supervision to improve the quality of learning. The principal carries out planning by setting goals and targets, preparing instruments and schedules, parties involved in preparing instruments and schedules, socialization, and preparing teacher administration. At the implementation stage, the principal checks the completeness of learning administration by visiting classes, diagnosing problems based on instruments, and determining problems and how to solve problems. At the follow-up stage, the principal analyzes the results of supervision, feedback, and meetings with teachers to provide continuous reinforcement and guidance